Management of pod rot of groundnut using new fungicide molecules under field condition: Management of pod rot of groundnut using new fungicide molecules under field condition - T HANAMANT; P NAGARAJU (Journal of Oilseeds Research, 2020)
Under field evaluation of different fungicides to manage pod rot in groundnut, minimum per cent incidence ofpod rot, maximum pod yield, haulm yield and test weight and least pod rot incidence (28.39 %) was obtained in the treatment combination of seed treatment with Trichoderma harzianum at 10 g/kg of seeds + soil drenching with propineb at 30 days after sowing and fluopyram 17.7 % + tebuconozole 17.7 % @ 0.2% at 60 days after sowing which recorded as compared to other treatments.